MENGUBAH SAMPAH MENJADI TABUNGAN : Edukasi Daur Ulang dan Menabung Melalui Celengan Botol Bekas Di Desa Guntung, Batu Bara - Mutia Syahara; Tiflatul Husna; Alya Sahputri Siregar; Ardini Jelita Rohmatika; Azizah Widya Shaharani; Waldi Agustinan (LPPI UMN AL WASHLIYAH, 2025)
This community service program aims to foster environmental awareness and a culture of saving among children in Guntung Village from an early age by creating piggy banks from used bottles. Students participating in the Community Service Program (KKN) act as facilitators, educators, and motivators to empower the village community, especially elementary school students. The program uses a participatory approach with creative training and educational outreach. Results show an increase in children's understanding of recycling and development of saving habits. This article also discusses the challenges encountered during implementation and sustainable strategies to maintain the program's impact.